1996
DOI: 10.1093/bja/76.1.111
|View full text |Cite
|
Sign up to set email alerts
|

A perfusion system for in vitro measurement of human cilia beat frequency

Abstract: We have designed and built a perfusion system and perfusion chamber to allow investigation of the effects of anaesthetic agents on human cilia in vitro. Using this system, samples of human respiratory cilia can be maintained in a stable and controlled environment for several hours. We measured cilia beat frequency of nasal respiratory epithelium from 10 healthy volunteers; cilia beat frequency was constant over a 4-h period, and measurements were found to be in good agreement with previously published work [1]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…In vitro studies on cilial function have indicated that temperature, humidity, and pH are all factors that can affect performance, 119,[122][123][124][125][126] although changes in vivo in these parameters are unlikely to be very significant within the nose, because rapidly adapting changes in mucosal blood flow, glandular secretion, and nasal patency maintain homeostasis. Other endogenous confounding factors are age, 127 sex, 128 posture, 129 exercise, 130 and sleep, 131 as well as neurotransmitters and neurohormones.…”
Section: Confounding Factorsmentioning
confidence: 99%
“…In vitro studies on cilial function have indicated that temperature, humidity, and pH are all factors that can affect performance, 119,[122][123][124][125][126] although changes in vivo in these parameters are unlikely to be very significant within the nose, because rapidly adapting changes in mucosal blood flow, glandular secretion, and nasal patency maintain homeostasis. Other endogenous confounding factors are age, 127 sex, 128 posture, 129 exercise, 130 and sleep, 131 as well as neurotransmitters and neurohormones.…”
Section: Confounding Factorsmentioning
confidence: 99%
“…Propofol is very unlikely to have been responsible for the decrease in ciliary beat frequency, as it has not been shown to affect ciliary beat frequency when given either as a bolus or as an infusion. 9,18,19 The concentration of iso¯urane (1±4%) administered was determined by clinical response; however, all patients in this study were given iso¯urane for at least 30 min. Previous studies have shown that there are no opiode receptors on the nasal mucosa, and that morphine does not alter ciliary beat frequency.…”
Section: Discussionmentioning
confidence: 99%
“…">Perfusion chambers: Closed perfusion chambers (Figure C) ensure a large control over the environment. They are sealed to avoid evaporation of the media, and they allow for laminar flow …”
Section: Respiratory Ciliated Samples Preparationmentioning
confidence: 99%